The influence of the physical therapist's clinical practice time on the perception of body stability of the traditional frontal plank exercise: a pilot study - Martins, Tamiris Beppler; Costella, Taís; Bastos, Rodrigo Bittencourt e; Botti, Mayane dos Santos Amorim; Parizotto, Patricia; França, Maria Elisa Duarte; Santos, Gilmar Moraes (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Background: The traditional frontal plank exercise has a greater demand for biomechanical stability and has been widely prescribed and used in the practice of health professionals and, verifying the influence of the time of clinical practice can contribute positively in the clinical, scientific and social scope. Objective: To verify the influence of the physical therapist's clinical practice time on the perception of body stability of the traditional frontal plank exercise. Method: Individuals were selected in a non-probabilistic and intentional way, constituting a sample of young male adults, with a body mass index within the normal range, with a self-reported level of moderate to advanced physical activity and with at least six months of previous training experience. of resistance. The subjects were instructed to perform the frontal plank for 30 seconds, seeking to maintain all the items in the description of the technique. No verbal commands and encouragement were given during the exercise in order to direct only the influence of the different times of clinical practice of the evaluators. At the end of the exercise, the two evaluators self-reported their feedback through a control sheet prepared by the researchers. Results: The sample of this study consisted of 10 participants, with a mean age of 30.6 years (±4.03). All were male, white, and had no history of trauma/injury. The evaluator with six months of experience pointed out that eight subjects performed the frontal plank with high stability, while the evaluator with six years of experience observed only three subjects with high stability in the execution of the exercise. Conclusion: The findings of this study showed that there is a tendency towards a difference in the proportions of perceptions of stability in the traditional frontal plank between physical therapists with six months and six years of clinical experience.